Transcriptional Analysis of FOXO1, C/EBP-α and PPAR-γ2 Genes and Their Association with Obesity-Related Insulin Resistance - Boughanem, Hatim; Cabrera-Mulero, Amanda; Millán-Gómez, Mercedes; Garrido-Sánchez, Lourdes; Cardona, Fernando; Tinahones, Francisco José; Moreno-Santos, Inmaculada; Macías-González, Manuel (Genes, 2019)
Background: Obesity is associated with several comorbid disorders, ranging from cardiovascular diseases to insulin resistance. In this context, visceral adipose tissue (VAT) seems to have a close connection with insulin resistance. In our study, we hypothesized that the expression profile of key adipogenic genes, such as proliferator-activated receptor γ type 2 (PPAR-γ2), CCAAT/enhancer-binding protein type α (C/EBP-α), and forkhead box protein class O type 1 (FOXO1) in VAT should shed light on their association with obesity-related insulin resistance. Methods: To test this idea, we studied the expression profile of C/EBP-α, FOXO1 and PPAR-γ2 in VAT from non-obese individuals, and low insulin (LIR-MO) and high insulin morbidly obese (HIR-MO) subjects, through a combination of RT-qPCR, co-immunoprecipitation, ELISA, Western blot analysis and EMSA assays. Results: Our results show that C/EBP-α and PPAR-γ2 were down-expressed in HIR-MO individuals, while FOXO1 was overexpressed. In addition, the PPAR-γ2–RXR-α heterodimer showed weak activity and bound weakly to the putative IGFBP-2–PPRE promoter sequence in VAT from HIR-MO subjects when compared with LIR-MO individuals. Conclusions: These results show that PPAR-γ2, C/EBP-α, FOXO1 and IGFBP-2 have a close relationship with insulin resistance in VAT of morbidly obese individuals.